Experimental and Computational Studies on the Formation of Thorium–Copper Heterobimetallics. Issue 39 (18th August 2016) - Yang, Pikun; Zhou, Enwei; Hou, Guohua; Zi, Guofu; Ding, Wanjian; Walter, Marc D.
Abstract: The formation of actinide–transition metal heterobimetallics mediated by a terminal actinide imido complex was comprehensively studied. The reaction of the thorium imido complex [(η 5 ‐C5 Me5 )2 Th=N(mesityl)(DMAP)] (3 ), prepared from [(η 5 ‐C5 Me5 )2 ThMe2 ] (1 ) and mesitylNH2 or [(η 5 ‐C5 Me5 )2 Th(NHmesityl)2 ] (2 ) in the presence of 4‐(dimethylamino)pyridine (DMAP), with copper(I) halides gave the first thorium–copper heterobimetallic compounds [(η 5 ‐C5 Me5 )2 Th(X)N(mesityl)Cu(DMAP)] (X=Cl (4 ), Br (5 ), I (6 )). Complexes4 –6 feature an unusual geometry with a short Th−Cu distance, which DFT studies attribute to a weak donor–acceptor bond from the Cu + atom to the electropositive Th 4+ atom. They are reactive species, as was shown by their reaction with the dimethyl complex [(η 5 ‐C5 Me5 )2 ThMe2 ] (1 ). Furthermore, a comparison between Th and early transition metals confirmed that Th 4+ exhibits distinctively different reactivity from d‐transition metals. Abstract : Time for thorium ! Experimental and computational studies revealed that the thorium–copper bond is best described as a weak donor–acceptor interaction between the electron‐rich Cu I and the electropositive Th IV atoms (see scheme).